HUBUNGAN SELF CARE DENGAN KUALITAS HIDUP PASIEN GAGAL JANTUNG DI RSD MANGUSADA - Laksmi, Ida Ayu Agung; Suprapta, Made Ani; Surinten, Ni Wayan (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Long term of heart failure symptoms will affect the patient functional status and ability to do self-care appropriately. Decreasing functional status and self-care ability will certainly affect the quality of life of patients. This study aimed to determine the relationship of self-care with the quality of life of heart failure patients that undergoing treatment at Heart Polyclinic of Mangusada Hospital. The research design was descriptive correlational using cross sectional approach. The study was conducted in January-February 2019. Total respondent participated were 61 respondents and were taken using a purposive sampling technique. Self care of heart index (SCHFI) questionnaire and the Minnesota Living With Heart Failure Questionnaire (MLHFQ) were used. The results showed that the average of self-care score was 45.25 and the average score of the quality of life was 60.67. Analysis using the Spearman Rank test obtained p-value = 0,000 and r = 0.506. It can be concluded that self care had a significant correlation on quality of life patients with heart failure in Mangusada Hospital. We recommended that nursing service providers play an active role in providing education and motivation to heart failure patients to improve self-care abilities.